A Study of Electrocyclic Reactions in a Molecular Junction: Mechanistic and Energetic Requirements for Switching in the Coulomb Blockade Regime. Issue 12 (12th June 2017) - Olsen, Stine T.; Brøndsted Nielsen, Mogens; Hansen, Thorsten; Ratner, Mark A.; Mikkelsen, Kurt V.
Abstract: The front cover artwork was made by Dr. Stine T. Olsen. The present work involves a long term collaboration between members of the Center for Exploitation of Solar Energy at the Department of Chemistry, University of Copenhagen, Denmark and one of its international partners from the Department of Chemistry, Northwestern University, U.S.A. Read the full text of the article at10.1002/cphc.201700140 . Abstract : "Molecular photoswitches incorporated in molecular junctions yield the possibility of light‐controlled switching of conductance due to the electronic difference of the photoisomers. Another isomerization mechanism, dark photoswitching, promoted by a voltage stimulus rather than by light, can be operative in the Coulomb blockade regime…" This and more about the story behind the front cover can be found in the Full Paper at10.1002/cphc.201700140 .